Mineral‐Templated 3D Graphene Architectures for Energy‐Efficient Electrodes. Issue 22 (2nd May 2018) - Zhang, Mingchao; Chen, Ke; Wang, Chunya; Jian, Muqiang; Yin, Zhe; Liu, Zhenglian; Hong, Guo; Liu, Zhongfan; Zhang, Yingying
Abstract: 3D graphene networks have shown extraordinary promise for high‐performance electrochemical devices. Herein, the chemical vapor deposition synthesis of a highly porous 3D graphene foam (3D‐GF) using naturally abundant calcined Iceland crystal as the template is reported. Intriguingly, the Iceland crystal transforms to CaO monolith with evenly distributed micro/meso/macropores through the releasing of CO2 at high temperature. Meanwhile, the hierarchical structure of the calcined template could be easily tuned under different calcination conditions. By precisely inheriting fine structure from the templates, the as‐prepared 3D‐GF possesses a tunable hierarchical porosity and low density. Thus, the hierarchical pores offer space for guest hybridization and provide an efficient pathway for ion/charge transport in typical energy conversion/storage systems. The 3D‐GF skeleton electrode hybridized with Ni(OH)2 /Co(OH)2 through an optimal electrodeposition condition exhibits a high specific capacitance of 2922.2 F g −1 at a scan rate of 10 mV s −1, and 2138.4 F g −1 at a discharge current density of 3.1 A g −1 . The hybrid 3D‐GF symmetry supercapacitor shows a high energy density of 83.0 Wh kg −1 at a power density of 1011.3 W kg −1 and 31.4 Wh kg −1 at a high power density of 18 845.2 W kg −1 . The facile fabrication process enables the mass production of hierarchical porous 3D‐GF for high‐performance supercapacitors. Abstract : A tunable hierarchical porous monolithic 3D graphene foam is synthesized by using calcined Iceland crystal as the template through chemical vapor deposition. The 3D graphene foam skeleton electrode hybridized with Ni(OH)2 /Co(OH)2 exhibits a high energy density of 83.0 Wh kg −1 at a power density of 1011.3 W kg −1 and 31.4 Wh kg −1 at a high power density of 18 845.2 W kg −1 .